The New Science of Axiological Psychology - Pomeroy, Leon (Value Inquiry Book Series ;, 2005)
This book uses scientific validity measures to create empirical value science and a normative new science of axiological psychology by integrating cognitive psychology with Robert S. Hartman's formal theory of axiological science. It reveals a scientific way to identify and rank human values, achieving values appreciation, values clarification, and values measurement for the twenty first century.